Semaphorin 3A Inhibits Inflammation in Chondrocytes under Excessive Mechanical Stress - Chikako Sumi; Naoto Hirose; Makoto Yanoshita; Mami Takano; Sayuri Nishiyama; Yuki Okamoto; Yuki Asakawa; Kotaro Tanimoto (Mediators of Inflammation)
Background. Excessive mechanical stress causes inflammation and destruction of cartilage and is considered one of the cause of osteoarthritis (OA). Expression of semaphorin 3A (Sema3A), which is an axon guidance molecule, has been confirmed in chondrocytes. However, there are few reports about Sema3A in chondrocytes, and the effects of Sema3A on inflammation in the cartilage are poorly understood. The aim of this study was to examine the role of Sema3A in inflammation caused by high magnitude cyclic tensile strain (CTS). Methods. Expression of Sema3A and its receptors neuropilin-1 (NRP-1) and plexin-A1 (PLXA1) in ATDC5 cells was examined by Western blot analysis. ATDC5 cells were subjected to CTS of 0.5 Hz, 10% elongation with added Sema3A for 3 h. Gene expression of IL-1β, TNF-ɑ, COX-2, MMP-3, and MMP-13 was examined by qPCR analysis. Furthermore, the phosphorylation of AKT, ERK, and NF-κB was detected by Western blot analysis. Results. Added Sema3A inhibited the gene expression of inflammatory cytokines upregulated by CTS in a dose-dependent manner. Addition of Sema3A suppressed the activation of AKT, ERK, and NF-κB in a dose-dependent manner. Conclusions. Sema3A reduces the gene expression of inflammatory cytokines by downregulating the activation of AKT, ERK, and NF-κB pathways in ATDC5 cells under CTS.